KEPASTIAN HUKUM PEMEGANG POLIS DALAM RENCANA PENYEHATAN KEUANGAN AJB BUMIPUTERA 1912: PROBLEMATIKA DAN PERLINDUNGAN HUKUM - Fajar Gilang Bripkano; Purwanto Purwanto; Febri Noor Hediati (Jurnal Ilmiah Advokasi, 2026)
Insurance functions as a risk management instrument that provides legal protection and certainty of rights for policyholders. However, in practice, the implementation of the Financial Recovery Plan (Rencana Penyehatan Keuangan/RPK) at AJB Bumiputera 1912 raises significant legal issues concerning the fulfillment of policyholders’ rights, particularly through the Policy Benefit Reduction (Penurunan Nilai Manfaat/PNM) scheme, which potentially disadvantages policyholders.This study aims to analyze the legal certainty of policyholders within the implementation of the RPK and to examine the available forms of legal protection. The research employs a normative juridical (doctrinal) method using statutory and conceptual approaches, supported by theories of legal certainty, insurance contracts, and risk transfer. The findings indicate that the implementation of the RPK has not provided adequate legal certainty for policyholders, as reflected in the suboptimal realization of the company’s financial obligations and the gap between projected and actual debt settlement outcomes. Furthermore, the application of the PNM scheme has created legal complications, particularly for policyholders who reject the scheme, resulting in the loss of membership status and limited participation in governance mechanisms, such as the election of the Policyholders’ Representative Body (BPA). This study highlights the existence of significant legal protection gaps for policyholders, emphasizing the need for stronger regulatory frameworks, more effective supervision, and dispute resolution mechanisms that ensure fairness and legal certainty within the insurance sector.Keywords: Legal Certainty, Policyholders, Mutual Insurance, Financial Recovery Plan